Comparison of measures to assess outcomes in total hip replacement surgery. Issue 2 (June 1996) - Dawson, J; Fitzpatrick, R; Murray, D; Carr, A
Abstract : OBJECTIVES–To compare the performance of a disease specific and a general health questionnaire in assessing changes resulting from total hip replacement. DESIGN–Two stage prospective study of patients undergoing total hip replacement surgery involving an assessment at a clinic before and six months after surgery. 60(32%) patients were followed up by post. SETTING–Outpatient departments at a specialist orthopaedic hospital and peripheral clinics within Oxfordshire. PATIENTS–188 patients admitted for unilateral total hip replacement between February and mid-August 1994. MAIN MEASURES–Patients' self assessed scores with the 12 item Oxford hip score and SF-36 general health questionnaire together with surgeons' assessment with Charnley hip score obtained before and again at six months after surgery. RESULTS–186 patients were followed up six months after total hip replacement; a subsample (n=60) by post. Of the 60 postal patients, 59(98.3%) fully completed the Oxford hip score compared with 44(73.3%) who fully completed the SF-36. For the followup sample as a whole, post operative changes in scores produced a large effect size of 2.75 on the Oxford hip score, compared with -1.89 physical function (SF-36), -2.13 pain (SF-36). With the exception of physical function and role (physical), postoperative SF-36 scores were shown to be similar to or better than those found by two population surveys on patients of comparable age. The responsiveness of a disease specific questionnaire, the Oxford hip score, and relevant sections of a general questionnaire, SF-36, were found to be similar as assessed by three different criteria. CONCLUSIONS–A disease specific questionnaire, the Oxford hip score, and a general state of health questionnaire, SF-36, performed similarly in assessing outcomes of total hip replacement except that the disease specific questionnaire resulted in a higher completion rate and greater responsiveness in some sections. On the other hand the general health questionnaire drew attention to broader problems of physical function not considered by the Oxford hip score. The health questionnaires examined here offer a valid and practical means of monitoring outcomes of hip replacement surgery.